2017
DOI: 10.1021/acs.langmuir.6b04308
|View full text |Cite
|
Sign up to set email alerts
|

Size Control of Silver-Core/Silica-Shell Nanoparticles Fabricated by Laser-Ablation-Assisted Chemical Reduction

Abstract: Aqueous colloidal silver nanoparticles have substantial potential in biological application as markers and antibacterial agents and in surface-enhanced Raman spectroscopy applications. A simple method of fabrication and encapsulation into an inert shell is of great importance today to make their use ubiquitous. Here we show that colloids of silver-core/silica-shell nanoparticles can be easily fabricated by a laser-ablation-assisted chemical reduction method and their sizes can be tuned in the range of 2.5 to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Recently, the approaches of PLAL and laser photochemical reduction have been combined into a single process through ablation of a solid target either immersed in or subsequently exposed to metal salt solution, in what is termed reactive laser ablation in liquid (RLAL) [10,[45][46][47][48][49][50][51][52]. RLAL has been widely used to generate metal-silica nanostructures, including Si/M (M = Ag, Au, Pd, Pt) core/shell NPs [47], Ag-core/silica-shell NPs [48], and large silica particles decorated with Au or Ag NPs [49]. While these RLAL reports have demonstrated the generation of hybrid semiconductor-metal nanocomposite materials in a single step, the metal-silica products are too large for catalysis applications such as CO oxidation that typically requires sub-5 nm metal NPs [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the approaches of PLAL and laser photochemical reduction have been combined into a single process through ablation of a solid target either immersed in or subsequently exposed to metal salt solution, in what is termed reactive laser ablation in liquid (RLAL) [10,[45][46][47][48][49][50][51][52]. RLAL has been widely used to generate metal-silica nanostructures, including Si/M (M = Ag, Au, Pd, Pt) core/shell NPs [47], Ag-core/silica-shell NPs [48], and large silica particles decorated with Au or Ag NPs [49]. While these RLAL reports have demonstrated the generation of hybrid semiconductor-metal nanocomposite materials in a single step, the metal-silica products are too large for catalysis applications such as CO oxidation that typically requires sub-5 nm metal NPs [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report a RLAL approach where a Si wafer immersed in a KAuCl 4 solution is ablated using sub-50 femtosecond (fs) laser pulses (fs-RLAL), producing significantly smaller silica-Au nanostructures than in previous reports using nanosecond lasers [47][48][49]. Using a high surface area support such as silica is commonly used to stabilize metal nanoparticles during catalytic reactions [60,61].…”
Section: Introductionmentioning
confidence: 99%
“…There are different pathways for synthesizing nanoparticles (NPs); however, it is a challenge for all of them to improve the control of physical properties of the nanostructures, since their behavior will largely depend on their characteristics (Fojtik et al 1993;Jiménez et al 2004;Pyatenko et al 2004;Popovici et al 2006;Pyatenko et al 2007;Jiménez et al 2008;Cobley et al 2009;Jiménez et al 2010;González-Castillo et al 2015;Ermakov et al 2017). In 2008, Jiménez et al demonstrated a novel hybrid physicalchemical method based on a chemical reaction assisted by laser ablation (Jiménez et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This method, assisted laser ablation (ALA), is basically a chemical synthesis (redox) where one of the reactants (silicon) is supplied in nanometer dimensions by laser ablation (Jiménez et al 2010). The laser ablation method is a powerful technique for producing nanostructured materials in different environments (Fojtik et al 1993;Jiménez et al 2004;Pyatenko et al 2004;Popovici et al 2006;Ermakov et al 2017). Recently, González-Castillo et al reported the synthesis of silver (Ag) NPs by ALA in two steps (González-Castillo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation